2016
DOI: 10.1007/s00296-016-3568-2
|View full text |Cite
|
Sign up to set email alerts
|

Fibromyalgia is associated to receiving chronic medications beyond appropriateness: a cross-sectional study

Abstract: The objectives of this study are to describe appropriateness and drug treatment of comorbidities in fibromyalgia (FM). Cross-sectional study of a group of patients. Number of drugs, indication, duration and appropriateness of prescriptions were evaluated. Patients were classified as: group 1, (FM/FM) previous FM diagnosis and fulfilling criteria; group 2, (noFM/noFM) other diagnosis and not fulfilling criteria; and group 3, (noFM/FM) other diagnosis but fulfilling criteria. Drugs were classified into drugs for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…A study from Spain, based on a telephone interview, found a usage rate of 16% for NSAIDs and 7.5% for opiates [ 43 ]. Studies based on actual purchases reported usage rates of 56–68% for NSAIDs and 14–56% for opiates [ 44 48 ]. Our findings show a higher rate of opiate use among FM patients in southern Israel than in the rest of the country [ 48 ] and one of the highest rates reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…A study from Spain, based on a telephone interview, found a usage rate of 16% for NSAIDs and 7.5% for opiates [ 43 ]. Studies based on actual purchases reported usage rates of 56–68% for NSAIDs and 14–56% for opiates [ 44 48 ]. Our findings show a higher rate of opiate use among FM patients in southern Israel than in the rest of the country [ 48 ] and one of the highest rates reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…They act at different levels. The main symptoms of the disease are generally treated with a pharmacological approach (Macfarlane et al, 2016), combined with a close monitoring of the eventual overuse or chronic use of drugs (Rivera & Vallejo, 2016). Another important step of the care is to provide education about the disease, the realistic goals that can be set during the treatment, the activities that have to be gradually introduced, the management of sleep and the communication with the others (Turk & Adams, 2016).…”
Section: Implications For the Treatmentmentioning
confidence: 99%